Rethinking connectivity: a case study of Covid-19 outbreak from China to Thailand - Limtrakoon, Pawarun (Thai Journal of East Asian Studies, 2020)
Due to the Covid-19 outbreak, which has been continually a hot issue on social media since the end of 2019. A massive flood of information, news, and individual point of views toward this situation have been playing an important role in shaping and constructing people’s perception within society. Especially in Thailand, a country which reasonably relies on the tourism industry as it has been taking part in impelling dynamics in society, tends to be affected by the outbreak. According to the centre of first outbreak is in Wuhan, a big city in China, where it seems to be far away from Thailand. I started to question on How the outbreak breaks in Thailand and how Thai society affected by Covid-19. Is Covid-19 a cause itself or People’s perception is? These questions link to Sociology theories and paradigms which i picked Mobility, Risk society, Stigma, and Social Interaction to frame a study, to explain the current situation and to deduce a tendency after detente of the outbreak. In this article is mostly information analytic by using many sources such as news from social media, related studies, and individual’s point of views through Twitter. Furthermore, collecting data on social media users individually by an online open questionnaire has been used in this article. Analysis revealed that the mobility of people cause a risk and spread out rapidly. But, the effect is likely caused by people’s perception and their behaviour toward the risk. In addition, those would bring about to a tendency of change in society. People are prone to have more awareness of their health and privacy to minimize risk that no-one knows when it would occur. As a result, this would lead to further travel behaviour that might have changed.